Perception of death and preference for end-of-life care among Asian Buddhists living in Montreal, Canada. Issue 8 (14th September 2022) - Dorji, Nidup; Lapierre, Sylvie
Abstract: Dying with dignity is important in Western culture. The aim of this qualitative study was to explore how Asian Buddhists, exposed to Western cultures, perceive death and dying with dignity, and examine their preferences for end-of-life care. We interviewed 15 Asian Buddhists living in Montreal (Canada). Participants regarded death as inevitable, while a good/dignified death had to be natural, peaceful, and, most of all, conscious. Most preferred palliative care to medical-aid-in-dying and emphasized death preparation through daily contemplation of impermanence. Care providers' understanding and respect of Buddhist patients' perception of a dignified death might help facilitate this important transition.